Climate change, gender, and nutrition linkages: Research priorities for Zambia - Ringler, Claudia; De Pinto, Alessandro; Choufani, Jowel; Theis, Sophie; Visocky, Mark; Harvey, Jeannie (International Food Policy Research Institute, 2017)
Climate change is a substantial threat to sustainable development in Zambia, a country experiencing weather hazards, drought and dry spells, seasonal and flash floods, and extreme temperatures that may well increase under climate change. Achieving the goals of Feed the Future and the Global Food Security Strategy requires careful consideration of the impact of relevant climate science on agricultural production, while at the same time considering other cross-cutting issues that influence agriculture-led poverty alleviation, resilience, and nutrition—such as gender. This policy note summarizes assessments of these linkages for Zambia under the Gender, Climate Change, and Nutrition Integration Initiative (GCAN)